LMI approach for robust stabilization of Takagi–Sugeno descriptor systems with input saturation. (5th April 2017) - Dang, Quoc Viet; Vermeiren, Laurent; Dequidt, Antoine; Dambrine, Michel
Abstract: The aim of this article is to present a systematic framework for the design of a robust controller for uncertain nonlinear systems represented in the Takagi–Sugeno descriptor form. The design takes explicitly into account state constraints and also the saturation of the control input. Based on Lyapunov theory, the tuning of the control parameters can be done by solving an optimization problem with linear matrix inequality constraints. Two numerical examples are included to illustrate the effectiveness of the proposed method.